2020
DOI: 10.11144/javeriana.upsy18-4.ardv
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la relación entre diferentes variables psicológicas en el contexto deportivo de los futbolistas

Abstract: En el rendimiento deportivo, influyen variables psicológicas como el clima motivacional, las orientaciones de meta, las necesidades psicológicas básicas del deporte y la cohesión del equipo. Este estudio plantea como objetivo examinar la relación entre este conjunto de variables psicológicas (clima motivacional, la orientación de meta, las necesidades psicológicas básicas del deporte y la cohesión) en varones y mujeres futbolistas. Participaron 175 futbolistas de entre 12 y 26 años (M = 15.59, DE = 2.8) que co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the contrary, high scores in ego involvement are associated with low scores in cohesion, a circumstance favored by the sociomotor space where the technical exercise in AGG takes place, limited in a small (13 × 13 m) and closed area, endorsed by previous studies Quested and Duda (2009), Iglesias et al (2019). This aspect was highlighted in previous research, where basketball, volleyball, and handball are more socially cohesive than sports that take place in a large area such as rugby and football (Rusu (2020), as well as in Castro-Sánchez et al (2019b) with judocas.…”
Section: Discussionmentioning
confidence: 81%
“…On the contrary, high scores in ego involvement are associated with low scores in cohesion, a circumstance favored by the sociomotor space where the technical exercise in AGG takes place, limited in a small (13 × 13 m) and closed area, endorsed by previous studies Quested and Duda (2009), Iglesias et al (2019). This aspect was highlighted in previous research, where basketball, volleyball, and handball are more socially cohesive than sports that take place in a large area such as rugby and football (Rusu (2020), as well as in Castro-Sánchez et al (2019b) with judocas.…”
Section: Discussionmentioning
confidence: 81%
“…like Amado et al (2019) concluded that team sports coaches should promote a perception of autonomy and competence in their athletes, with the aim of enhancing more positive self-talk and selfmotivational processes in competition, which promote better personal and team performance and well-being. Iglesias et al (2020) pointed out that teammates who help each other to progress, together with the union and teamwork enhanced by the coach's message, produce an increase in autonomy, feel more competent by knowing their roles and focusing on their function, and maintain much more enriched social relationships. Li et al (2019), in a study with 271 different athletes, found that a climate built around the tasks set by the coach and teammates, enhanced the feeling of competence and self-improvement as a goal, positively affecting athletes' mental strength.…”
Section: Discussionmentioning
confidence: 99%
“… Iglesias et al (2020) pointed out that teammates who help each other to progress, together with the union and teamwork enhanced by the coach's message, produce an increase in autonomy, feel more competent by knowing their roles and focusing on their function, and maintain much more enriched social relationships. Li et al (2019), in a study with 271 different athletes, found that a climate built around the tasks set by the coach and teammates, enhanced the feeling of competence and self-improvement as a goal, positively affecting athletes’ mental strength.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that both types of climate correlated negatively at the opposite end of a continuum. However, given the negative correlation between mastery climate and execution climate, it is appropriate, in a collective sport such as soccer, to enhance the climate of mastery, especially because the presence of a climate of execution would imply the predominance of individual objectives focused solely on the self [31]. The results of the relation between motivational climate and goal orientations indicated that mastery climate was positively related to goal orientation to the task and negatively related to goal orientation to the ego [32].…”
Section: Discussionmentioning
confidence: 99%
“…All belonged to professional clubs of the Spanish soccer league, in which, beginning in the initial categories, the footballers not only compete with external teams but also with members of their own team or companions (to enjoy more minutes, more matches, promotion, etc.). This context influences the different dispositional variables of the sportsman [31], as happens with extroversion, as the player advances to higher categories.…”
Section: Discussionmentioning
confidence: 99%